Challenges of Glycemic Control in COVID-19 Patients with Diabetes Mellitus in Resource-poor Settings - A., Esan; T. A., Azeez (International Journal of Innovative Research in Medical Science, 2020)
Background and objectives: Coronavirus disease 2019 is now a global pandemic affecting most countries in the world. Some conditions, such as diabetes mellitus, are associated with increased morbidity and mortality among COVID-19 patients. Poor glycemic control has been associated with the risk of contracting COVID-19 and it is also poor prognostic factors among patients infected. Therefore, all efforts should be focused on glycemic control especially among COVID-19 patients who also have diabetes. In the COVID-19 era however, getting a good glycemic control is faced with myriads of challenges. These challenges cut across different phases of the infection from a patient living with diabetes who has mild COVID-19 and is being managed at home to a critically ill patient with COVID-19. These challenges need to be identified and elaborated upon so as to device mechanisms to effectively address them. The aim of this review article is to highlight the various challenges of achieving a good glycemic control among COVID-19 patients who have diabetes. Relevant articles were gotten from PubMed, Google scholar, science direct as well as the grey literature using search terms such as ‘diabetes, covid 19’, ‘glycemic control, covid 19’, covid 19, resource-poor settings’.